2002
DOI: 10.1089/154099902762203722
|View full text |Cite
|
Sign up to set email alerts
|

The Risk for Infant Mortality among Adolescent Childbearing Groups

Abstract: Childbearing in < or =15-year-olds is associated with a substantial increased risk for infant mortality compared with childbearing in older adolescence. This study suggests that not reporting the father on a birth certificate is a potential risk marker. Risk differences among adolescent age groups may be important to consider when creating tailored intervention and prevention strategies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
26
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 21 publications
(19 reference statements)
0
26
1
Order By: Relevance
“…We also include the percentage of the state population aged 15-19 years, because young mothers experience more difficult pregnancies (Phipps, Sowers, and DeMonner 2002). We add a measure of the abortion rate to control for the possibility that abortion might be a way to prevent postbirth mortality (see Gruber, Levine, and Staiger 1999).…”
Section: Resultsmentioning
confidence: 99%
“…We also include the percentage of the state population aged 15-19 years, because young mothers experience more difficult pregnancies (Phipps, Sowers, and DeMonner 2002). We add a measure of the abortion rate to control for the possibility that abortion might be a way to prevent postbirth mortality (see Gruber, Levine, and Staiger 1999).…”
Section: Resultsmentioning
confidence: 99%
“…The rate for 15-19-year-old girls was 10.0%, whereas the overall rate was for all women was 8.2%. Teens less than 15 years of age are at a particularly high risk, although such pregnancies are fairly rare (8)(9)(10).…”
mentioning
confidence: 99%
“…This study corroborated the findings of Phipps et al, who evaluated the risk of infant mortality (defined as death within the first year after live birth) in a US birth cohort from the National Center for Health Statistics from 1995 to 1996. 71 The analysis included more than 700 000 single births. Of these births to women 12 through 19 years of age, there were 4631 infant deaths.…”
Section: Medical and Psychosocial Risks To The Infantmentioning
confidence: 99%
“…The risk of infant mortality was 1.6 (95% CI, 1.4-1.7) times greater for those with teen mothers younger than 15 years than for those with mothers 18 through 19 years old-a 56% greater risk. 71 Another study by Gilbert and associates 74 reported an increased risk of negative health outcomes for infants and adolescent parents. They examined birth and death certificates by using maternal and neonatal hospital discharge records of primiparous women (11-29 years of age) in California who delivered between January 1, 1992, and December 31, 1997.…”
Section: Medical and Psychosocial Risks To The Infantmentioning
confidence: 99%